Language and cognition in bilinguals and multilinguals : an introduction - Groot, A. M. B. de (Psychology Press, 2011)
This introductory level textbook comprehensively covers the psycholinguistic study of bilingualism and multilingualism, including traditional and brain-based approaches. Each chapter covers a key series of topics in clear, accessible language, and includes a description of the relevant methodological issues.